Importance of SLC26 Transmembrane Anion Exchangers in Sperm Post-testicular Maturation and Fertilization Potential - Touré, Aminata (Frontiers in Cell and Developmental Biology, 2019)
In mammals, sperm cells produced within the testis are structurally differentiated but remain immotile and are unable to fertilize the oocyte unless they undergo a series of maturation events during their transit in the male and female genital tracts. This post-testicular functional maturation is known to rely on the micro-environment of both male and female genital tracts, and is tightly controlled by the pH of their luminal milieus. In particular, within the epididymis, the establishment of a low bicarbonate (HCO3-) concentration contributes to luminal acidification, which is necessary for sperm maturation and subsequent storage in a quiescent state. Following ejaculation, sperm is exposed to the basic pH of the female genital tract and bicarbonate (HCO3-), calcium (Ca2+) and chloride (Cl-) influxes induce biochemical and electrophysiological changes to the sperm cells (cytoplasmic alkalinization, increased cAMP concentration and protein phosphorylation cascades), which are indispensable for the acquisition of fertilization potential, a process called capacitation. Solute carrier 26 (SLC26) members are conserved membranous proteins that mediate the transport of various anions across the plasma membrane of epithelial cells and constitute important regulators of pH and HCO3- concentration. Most SLC26 members were shown to physically interact and cooperate with the Cystic Fibrosis Transmembrane conductance Regulator channel (CFTR) in various epithelia, mainly by stimulating its Cl- channel activity. Among SLC26 members, the function of SLC26A3, A6 and A8 were particularly investigated in the male genital tract and the sperm cells. In this review, we will focus on SLC26s contributions to ionic- and pH-dependent processes during sperm post-testicular maturation. We will specify the current knowledge regarding their functions, based on data from the literature generated by means of in vitro and in vivo studies in knock-out mouse models together with genetic studies of infertile patients. We will also discuss the limits of those studies, the current research gaps and identify some key points for potential developments in this field.